Postauricular Melanocytic Neuroectodermal Tumor of Infancy: A Rare Site of a Rare Tumor—MNTI as a Postauricular Mass with Literature Review. (5th July 2018) - Evans, S.; Woolley, A.
Abstract : Melanocytic neuroectodermal tumor of infancy (MNTI) is a rare osteolytic neoplasm of neural crest cell origin. There are less than 500 documented cases, most frequently affecting the maxilla of infants less than 1 year old. We present a unique case of a two-month-old male with a progressive postauricular mass since birth, confirmed to be a MNTI. The lesion required three resections over the course of five months, with rapid recurrence ultimately requiring a craniectomy, highlighting the difficulty in treating these tumors. Histological and radiographic features were reviewed; an updated literature review for identifying and treating these lesions is presented.